Inflammable drops a constructivist approach - Pimentel, Jorge Roberto; Saad, Fuad Daher; Yamamura, Paulo; Furukawa, Claudio Hiroyuki (Caderno Brasileiro de Ensino de Física, 2005)
This paper suggests a very simple set-up that allows an amazing demonstrationin Physics high-school classes: the phenomena of liquid oxygen condensation on a surface refrigerated with liquid nitrogen. Thedemonstration involves an unusual effect and its purpose is to serve asan inducing element for constructivist learning allowing the students toanalyze it, discuss it, formulate hypothesis and finally to achieve a correctexplanation for the observed phenomena.